The Influence Of Employees’ Spiritual Intelligence On Organizational Citizenship Behavior: The Moderating Role Of Islamic Work Ethic - Ahmed, Adeel (2018)
The main objective of this study is to investigate the impact of employees’ spiritual intelligence (i.e., sense of meaning, sense of community and wisdom) on organizational citizenship behavior (OCB). This study investigates the moderating effect of the Islamic work ethic between the relationship of the dimensions of spiritual intelligence and organizational citizenship behavior. The lack of organizational citizenship behavior among employees is considered as one of the main problems contributed to the low performance of employees of airline industry in Pakistan.